(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2025)
This essay discusses some problematic issues on listening studies in Communication, with a special focus on relations with the fields of Aesthetics and Performance Studies. Recognizing the trajectory and transformations of the listening concept, we point out three axes on which the relationships between listening and communication are anchored: the debate on performance; the very notion of experience; and the crafts of listening as a critical and inventive fabulation of possible futures and existences. In the end, we point to the power of studies that focus on oratures, oralitures and listening as conditions for the possibility of apprehension of what escapes the discourse.